Classification Of Bll Blazars By Optical Activity Types - Mickaelian, A. M.; Abrahamyan, H. V.; Paronyan, G. M.; Mikayelyan, G. A.; Sukiasyan, A. G.; Mkrtchyan, V. K.
We have carried out a spectral classification by the Activity Types for a subsample of Blazars from the BZCAT v.5 Catalogue, namely the BL Lac (BLL, Lacertids) candidates, designated in the Catalogue as BZB subtype objects. The classification is based on the Sloan Digital Sky Survey (SDSS) homogeneous medium-resolution optical spectroscopy and along with the standard BPTtype diagnostic diagrams, we have applied our newly introduced fine classification scheme with subtypes of Quasars and considering many more features. Out of 1151 BZB objects, 552 having SDSS spectra were classified. After new classification, 259 (46.1%) of 552 have not changed their optical class, and 293 (53.1%) of these objects have changed their optical class. Having this new information on the optical classification we suggest to change the classification of some objects in BZCAT: for 130 BZB objects to BZG, for 18 BZB objects to BZQ and for 145 BZB objects to BZU.
Keywords: Astrophysics